Impact of exercise and leucine-enriched protein supplementation on physical function, body composition, and inflammation in pre-frail older adults: a quasi-experimental study - Merchant, Reshma Aziz; Chan, Yiong Huak; Anbarasan, Denishkrshna; Seetharaman, Santhosh; Au, Lydia; Nachammai, Vidhya; Lai, Alexa; Ho, Vanda; Wong, Beatrix Ling Ling; Pang, Eunice; Bhaskaran, Kalpana (Frontiers in Medicine, 2023)
Background: Exercise and protein enriched diet are essential for muscle protein synthesis, cellular growth, mitochondrial and immune function. The US Food and Nutrition Board's current guideline on recommended dietary allowance for protein in older adult is 0.8g/kg per day which may not be sufficient in vulnerable pre-frail older adults. Aims: This study aimed to evaluate impact of leucineenriched protein supplementation with or without exercise over 3 months in pre-frail older adults who consumed ≤ 1g/kg/day of protein in improving i) physical function ii) body composition measures iii) inflammatory biomarkers such as Interleukin-6 (IL-6) and Tumor Necrosis Factor Alpha (TNF-α). Methods: Non-randomized cluster quasi-experimental study guided by the STROBE checklist of 178 pre-frail older adults (112 control, 44 nutrition (Nu) and 22 in the nutrition with exercise (Nu+Ex) group) comparing the effect of Nu+Ex and Nu on physical function, body composition and inflammation. At 0, 3 and 6 months, questionnaires on demographics, depression, perceived health, and cognition were administered. Physical function assessment (short physical performance battery (SPPB) test, gait speed, handgrip strength, 5x sit to stand (STS)) was conducted and body composition analysis was performed using bioelectrical impedance analysis machine. IL-6 and TNF-α were measured at 0 and 3 months. Results: At 3 months, there were significant improvements in gait speed, 5x STS, SPPB scores, depression, perceived health, fat free mass and appendicular skeletal muscle mass indices in the Nu+Ex group. Both Nu+Ex and Nu groups had improvements in body cell mass and reduction in IL-6 and TNF-α. The improvements were not sustained at 6 months. Conclusions: Our study results need to be validated in future longitudinal randomized studies with larger sample size focusing on population at risk.